Study to Measure the impact of Pharmacists and Pharmacy Services (STOMPP) on Medication Non-Adherence: Medication Adherence and Clinical Outcomes - Sharrel Pinto, BS Pharm, DMM, MS, PhD; Angela Simon, PharmD Candidate 2018, MS Candidate 2018; Feyikemi Osundina, PharmD, MS; Matthew Jordan, PharmD, MS; Diana Ching, PharmD, MS Candidate 2019 (University of Minnesota Libraries Publishing, 2018)
Objective: To compare the impact of various pharmacy-based services on medication adherence and clinical outcomes. Design: Prospective, randomized control trial Setting: A local endocrinology group (clinic setting) and community pharmacies belonging to a regional integrated delivery network (IDN) in Toledo, OH Population: Subjects included within this study had type 2 diabetes, were prescribed a minimum of five medications, at least 18 years of age, having the ability to self-administer medications as prescribed, and be able to speak and understand English. Subjects were required to have Paramount health insurance, must be willing and able to provide informed consent, actively participate in the assigned MTM sessions, and have adequate transportation to attend the sessions at a participating pharmacy.  Methods: Patients were recruited through flyers at practice sites, referrals from physicians and pharmacists, and direct mailers. Members of the research team would screen patients to assess their eligibility to participate in the study. Patients who fit the inclusion criteria were randomized into one of the following four different groups: Pill Bottle (PB), Blister Pack (BP), Pill Bottle + Medication Therapy Management (PB+MTM), and Adherence Pharmacy (BP+MTM). Patients enrolled in the BP groups had their medications synchronized. Patients in the AP group were given the option to have their medications delivered, if needed. Practice innovation: We partnered with a regional integrated delivery network (IDN) with multiple community pharmacy practice sites and a practice group of endocrinologists. A new practice model called Adherence Pharmacy was conceptualized and implemented within the community setting and was accessible to patients. Main Outcomes Measures: Medication adherence, measured using proportions of days covered (PDC) and pill count scores at baseline, 3 months, 6 months, 9 months, and 12 months; Hemoglobin A1c (HbA1c), body mass index (BMI), systolic blood pressure (SBP), and diastolic blood pressures (DBP) were collected at baseline, 6 months, and 12 months Results: A mixed-model ANOVA was used to study the impact of these services on medication adherence, using PDC and pill count scores. Results of the 61 patients in the study revealed that there was a statistically significant difference between the PB and BP groups (p=0.008); between the PB and BP+MTM groups (p=0.023); and between the PB+MTM and the BP+MTM groups (p=0.041). Except at baseline, adherence scores at all time points (0, 3, 6, 9, and 12 months) were significant with the patients in the BP and BP+MTM groups having higher adherence compared to those in the PB and PB+MTM groups. Pill count scores had similar results to the PDC measures. Insert data from HBA1c, BMI, SBP and DBP. Clinical outcomes were also analyzed using the mixed between-within ANOVA and were measured at baseline, 6, and 12 months. Patients in the MTM groups reached the American Diabetes Association goal of 7%, whereas the patients in the PB group did not reach a goal at 12 months. All groups, except for the PB only group, indicated a statistically significant change from baseline to 12 months. When comparing body mass index (BMI) scores across groups over time, patients in the BP+MTM group showed the lowest BMI at 12 months. There were not any significant differences across the groups, but patients in the two MTM groups saw greater improvement in their BMI scores than patients in the other two groups. There were no significant differences between groups in SBP and DBP reduction. However, patients in the two BP groups reached a SBP goal sooner (per the Eighth Joint National Committee) than patients in the PB+MTM and PB groups. Conclusion: Patients had improved clinical outcomes and adherence rates when using blister packaging and medication therapy management services, individually and in combination. Blister packaging seemed to have a greater impact on medication adherence while MTM services helped improve clinical endpoints. However, patients who received the combination of services offered within the AP demonstrated higher improved clinical outcomes and adherence rates when compared to patients who did not. While each of these services was found to be more impactful that dispensing medications in pill bottles, combining them can provide a greater benefit to patients.   Type: Original Research